The proliferation of belatacept‐resistant T cells requires early IFNα pathway activation. Issue 2 (22nd September 2021) - Herr, Florence; Desterke, Christophe; Bargiel, Karen; Vernochet, Amelia; Vanhove, Bernard; Vadanici, Radu; Ye, Fan; Dekeyser, Manon; Durrbach, Antoine
Abstract : Belatacept was developed to replace calcineurin inhibitors in kidney transplantation. Its use is associated with better kidney transplant function, a lower incidence of anti‐donor antibodies and higher graft survival. However, it is also associated with a higher risk of cellular rejection. We studied the activation and proliferation mechanisms of belatacept‐resistant T lymphocytes (TLs), to identify new pathways for control. We performed a transcriptomic analysis on CD4 + CD57 + PD1 − memory TLs, which are responsible for a higher incidence of graft rejection, after allogeneic stimulation with activated dendritic cells (aDCs) in the presence or absence of belatacept. After six hours of contact with aDCs, the (CD4 + CD57 + PD1 − ) (CD4 + CD57 + PD1 + ) and (CD4 + CD57 − ) lymphocytes had different transcriptional profiles with or without belatacept. In the CD4 + CD57 + PD1 − population, the IFNα‐dependent activation pathway was positively overrepresented, and IRF7 transcript levels were high. IRF7 was associated with IFNα/β and IL‐6 regulation. The inhibition of both these cytokines in a context of belatacept treatment inhibited the proliferation of CD4 + CD57 + PD1 − T cells. Our results show that IRF7 is rapidly upregulated in belatacept‐resistant CD4 + CD57 + PD1 − TLs. The inhibition of type I IFN or IL‐6 in association with belatacept treatment reduces the proliferation of belatacept‐resistant TLs, paving the way for new treatments for use in organ transplantation. Abstract : Belatacept resistant CD4+CD57+PD1‐ T lymphocyte activation, which is involved in renal graft rejection, is induced by the association of CD28 and interferon alpha or interleukin‐6 signals in humans and can be inhibited by corresponding blocking antibodies.